Tailoring Ti3C2Tx MXene multilayers for biomaterial integration: synthesis, characterization, and cytotoxicity - Yaman, Pasa; Kucukyildirim, Bedri Onur (ELSEVIER, 2026)
This study examines the biomedical potential of Ti3C2Tx MXene multilayers, which are synthesized from the Ti3AlC2 MAX phase using different wet chemical etching methods: HF, LiF/HCl, and NaF/HCl. The effects of each etchant on the morphology, interlayer spacing, surface terminations, and defect structures are thoroughly analyzed using techniques such as XRD, FESEM, EDS, FTIR, and Raman spectroscopy. Cytotoxicity tests based on assays using L929 fibroblast cells demonstrate a strong relationship between surface groups and biocompatibility. Among the tested variants, NaF/HCl-etched MXenes showed smoother multilayers with less structural damage, optimized surface terminations, and lower toxicity to cells compared to HF-etched multilayers, which exhibited more structural damage, surface oxidation, and higher toxicity. These results highlight the importance of selecting the right etching method in tailoring MXene multilayers for use in ceramic-based biomedical scaffolds and implantable devices, offering guidance for future development of biocompatible materials.
Keywords: MXene; Wet chemical etching; Biocompatibility; Mouse fibroblast cells; EXFOLIATION; NANOSHEETS; CRYSTAL; Materials Science; Physics